The State of Irreversible Electroporation in Interventional Oncology - Silk, Mikhail (Thieme Medical Publishers, 2014)
A new ablation modality, irreversible electroporation (IRE), has been of increasing interest in interventional radiology. Its nonthermal mechanism of action of killing tumor cells allows physicians the ability to ablate tumors in areas previously contraindicated for thermal ablation. This article reviews the current published clinical outcomes, imaging follow-up, and the current knowledge gaps in the procedure for patients treated with IRE.